2021
DOI: 10.1037/amp0000779
|View full text |Cite
|
Sign up to set email alerts
|

Translating cultural assets research into action to mitigate adverse childhood experience–related health disparities among African American youth.

Abstract: Adverse childhood experiences (ACEs) including trauma exposure, parent mental health problems, family dysfunction, and community-level adversities put individuals at risk for a host of negative health outcomes. The effects of cumulative ACEs are numerous, diverse, and can predispose an individual to cognitive, emotional, behavioral, and physical health problems as well as premature death. African American youth experience disproportionate exposure to ACEs in the context of racism that increases risk for allost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 94 publications
0
14
0
Order By: Relevance
“…Communalism is a cultural orientation towards interdependence (and thought to stand in contrast to the Eurocentric value of independence) that emphasizes social bonds, social duties, and the importance of collective well-being, both outside and within one's family (i.e., familism) (Abdou et al, 2010;Schwartz et al, 2010). Communalism has been highlighted by researchers as a potential culturally specific resilience-promoting asset for racially/ethnically diverse populations, including Black, Latinx/Hispanic, and Asian American groups (Moemeka, 1998;Schwartz et al, 2010;Woods-Jaeger et al, 2021). However, evidence has been mixed in its level of support for this hypothesis (Abdou et al, 2010;Gaylord-Harden & Cunningham, 2009;Harris & Molock, 2000), and some scholars have suggested that higher levels of communalism may sensitize one to the presence of stressors such as discrimination (Goldston et al, 2008;Perez-Brena et al, 2018).…”
Section: Resilience-promoting Factorsmentioning
confidence: 99%
“…Communalism is a cultural orientation towards interdependence (and thought to stand in contrast to the Eurocentric value of independence) that emphasizes social bonds, social duties, and the importance of collective well-being, both outside and within one's family (i.e., familism) (Abdou et al, 2010;Schwartz et al, 2010). Communalism has been highlighted by researchers as a potential culturally specific resilience-promoting asset for racially/ethnically diverse populations, including Black, Latinx/Hispanic, and Asian American groups (Moemeka, 1998;Schwartz et al, 2010;Woods-Jaeger et al, 2021). However, evidence has been mixed in its level of support for this hypothesis (Abdou et al, 2010;Gaylord-Harden & Cunningham, 2009;Harris & Molock, 2000), and some scholars have suggested that higher levels of communalism may sensitize one to the presence of stressors such as discrimination (Goldston et al, 2008;Perez-Brena et al, 2018).…”
Section: Resilience-promoting Factorsmentioning
confidence: 99%
“…Noting the impact of historical trauma on African Americans, Hampton-Anderson et al (2021) explore the unique needs of this population through a biopsychosocial-cultural framework, and make recommendations for effective responses relative to ACEs. Woods-Jaeger et al (2021) expand this discussion to examine culture as a source of protective factors for African American youth and offer strategies for responding to ACEs that account for the context of racism.…”
Section: Critical Questionsmentioning
confidence: 99%
“…Continuous encounters of racism within the workplace affect the physical and mental well-being of employees (Memon et al, 2016). Everyday events such as threats, being treated with less respect, or being thought of as having lower intelligence due to race, constitute chronic racism (Woods-Jaegar et al, 2021). It is known that racism can lead to physical and mental health challenges such as chronic and acute forms of stress (Novacek et al, 2020).…”
Section: The Impact Of Hostile Contexts On Black Faculty's Mental Healthmentioning
confidence: 99%
“…It is known that racism can lead to physical and mental health challenges such as chronic and acute forms of stress (Novacek et al, 2020). In Black individuals, stress caused by racism manifests as hypertension, depression, anxiety, psychological distress, and low self-esteem (Woods-Jaegar et al, 2021). Chronic racism characterizes the experiences of many Black faculty within higher education.…”
Section: The Impact Of Hostile Contexts On Black Faculty's Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation